Associations Between Cancer-Related Self-Efficacy, Coping Styles, and Perceived Stress in Patients with Lung Cancer: A Cross-Sectional Mediation Analysis - Agata Poręba-Chabros; Magdalena Kolańska-Stronka; Marzanna Farnicka (Journal of Clinical Medicine, 2026)
Lung cancer carries a substantial psychosocial burden, frequently involving elevated psychological distress, disease-related stigma, and difficulties in adaptation to illness. Coping styles and self-efficacy are both recognized as relevant personal resources in chronic illness, but their combined statistical association with perceived stress, and specifically whether self-efficacy accounts for part of the association between coping and stress, has not been examined in lung cancer patients. Objective: This study examined the statistical associations between coping styles (task-, emotion-, and avoidance-oriented), cancer-related self-efficacy, and perceived stress, testing cancer-related self-efficacy as a mediator of each coping style’s association with perceived stress, and additionally compared these variables by gender. Methods: A cross-sectional study was conducted among ninety-seven patients diagnosed with lung cancer. Standardized measures included the Coping Inventory for Stressful Situations, a cancer-specific adaptation of the Generalized Self-Efficacy Scale, and the Perceived Stress Scale. A series of three simple mediation analyses was performed to evaluate the proposed statistical model. Results: Task-oriented coping was positively, and emotion-oriented coping negatively, associated with cancer-related self-efficacy; avoidance-oriented coping showed no significant association with self-efficacy. Task- and emotion-oriented coping were significantly associated with perceived stress in the expected directions, while avoidance-oriented coping was not. Cancer-related self-efficacy significantly, and partially, mediated the association between task-oriented coping and perceived stress; no significant indirect effect was found for emotion- or avoidance-oriented coping. Women reported significantly higher perceived stress and greater use of emotion-oriented coping than men, with no significant gender differences in self-efficacy or the other coping styles. Conclusions: In this cross-sectional sample, cancer-related self-efficacy was statistically associated with lower perceived stress specifically through its association with task-oriented coping, whereas the association between emotion-oriented coping and stress appeared largely independent of self-efficacy. These findings suggest that coping styles are associated with perceived stress through at least partly distinct mechanisms and support attention to both active coping and self-efficacy beliefs in psychosocial care for lung cancer patients, while findings regarding gender differences warrant further, formally tested investigation.